HUBUNGAN KECANDUAN BERMAIN GAME ONLINE PADA SMARTPHONE DENGAN KUALITAS TIDUR SISWA SMAN 1 KERUAK TAHUN 2020 - Panji Wage Kosasih; Danang Nur Adiwibawa; Irwan Syuhada; Yolly Dahlia (Nusantara Hasana Journal, 2022)
World Health Organization (WHO) in 2018 classifies addiction playing online game into the International Classification of Disease11th/ ICD-11). Addicted to playing online games is defined as a pattern ofbehavior gaming or playing ("digital-gaming" or "video-gaming") which has the characteristics, namely the disruption of self-control ability due to playing games. Give priority to games over other activities in daily life; this happens continuously and the intensity increases which causes dependency, sleep disturbance, social disturbance (withdrawal, wasting money) and can interfere with activity. Research objective to determine the relationship of addiction playing online games on smartphones with the sleep quality of students sman 1 keruak in 2020. This research is observational analytic with design cross sectional. The sampling technique uses purposive sampling. The study was conducted at Keruak 1 High School in November 2020. The research subjects were in class 12th students of SMAN 1 Keruak in 2020 with a total of 160 respondents, then conducted interviews using the Ten-Item Internet Gaming Disorder Test (IGDT-10) questionnaire to determine addictions or not addicted to online games and conducted interviews using the Pittsburgh Sleep Quality Index (PSQI) questionnaire to obtain secondary data. The data obtained were analyzed by correlation test Spearman Rank. The limit of significance (p) is p ≤ 0.05. The analysis results obtained a significance value (p) of 0.000 and a correlation coefficient (r) of 0.548 which indicates a significant relationship between addiction to playing online games and sleep quality in high school students, and the direction of the positive correlation. There is a relationship between addiction to playing online games on smartphones and the quality of sleep for grade 12 students of SMAN 1 Keruak in 2020.